Risk characterization of microbiological hazards in food : guidelines. - World Health Organization; Food and Agriculture Organization of the United Nations (Geneva, Switzerland : World Health Organization ; Rome, Italy : Food and Agriculture Organization of the United Nations, 2009)
These guidelines provide descriptive guidance on how to conduct risk characterization in various contexts, and utilizing a variety of tools and techniques. They have been developed in recognition of the fact that a reliable estimation of risk is critical to the overall risk assessment. This volume contains information that is useful to both risk assessors and risk managers, governments and food regulatory agencies, scientists, food producers and industries and other people or institutions with an interest in the area of microbiological hazards in food, their impact on human health and food trade and their control.--Publisher's description.
Introduction -- Purpose of microbiological food safety risk assessment -- Qualitative risk characterization in risk assessment -- Semi-quantitative risk characterization -- Quantitative risk characterization -- Quality assurance -- Linking risk assessment and economic analysis -- Risk communication and aspects of risk characterization.
"The development of these guidelines was by the Secretariat of the Joint WHO/FAO Expert Meetings on Microbiological Risk Assessment (JEMRA)"--P. vii.
Includes bibliographical references (p. [109]-113).
Also available online.
Keywords: Foodborne diseases; Food contamination -- Risk assessment; Food -- Microbiology; Health risk assessment; Food industry and trade -- Risk management; Food Microbiology; Food Contamination; Water Microbiology; Risk Assessment -- methods; Risk Management; Guideline